KONTRIBUSI BOYGROUP NCT 127 DALAM MENYEBARKAN KONSEP SOFT MASCULINITY DI INDONESIA PADA TAHUN 2019-2021 - Marsya Salsabila Zahra, (2023)
International Relations is a field that produces and maintains masculinity which is represented through physical characteristics, up to power. However, popular culture now has a significant role in shaping representations of gender identity. The author analyzes using social construction theory, the concept of postmodern feminism, the concept of popular culture, and the concept of soft masculinity. The type of research used is qualitative descriptive research using interview techniques and literature study. As for the results obtained from this research, research sources saw that there are different social constructions in Indonesian society regarding the phenomenon of soft masculinity through their experiences and interactions with South Korean K-Pop culture. This change in views was influenced by the actions taken by NCT 127. From the analysis of the answers given by respondents, several things can be concluded, namely through physical appearance, visual appearance, personality, and behavior of NCT 127. The difference in gender concepts between Indonesia and South Korea has a gap the big one. What NCT 127 shows is unusual in Indonesia, and the presence of soft masculinity provides a new perspective on the concept of gender masculinity in Indonesia.